An analysis of the meanings of consumption of wine in a wine association for women context - Bertuol, Mariana; Sampaio, Claudio Hoffmann; Perin, Marcelo Gattermann; Vieira, Marcia Horowitz (Revista de Administração da UFSM, 2017)
The products usefulness it is not the only decisive factor when consumers are deciding whether to buy or not a product, given the fact that the symbolism behind the products meaning also play an important role in this process. These meanings can be idiosyncratic as it can be shared by other consumers. Besides it can be used by the individuals to maintain their identity or to create a whole new identity to represent themselves in the eyes of the society. This study aimed to understand the construction process of the meaning of wine consume by a group of women who share habits, tastes and opinions which lead to the creation of a wine association for women only , in the “Serra Gaucha”. This article´s main objective was to understand the women’s wine association influence over the construction process of the meanings of wine consumption. In order to achieve this study purpose, a qualitative and exploratory research was conducted. Between the main results of this research, it is clear how the wine association for women plays a key role in its member life style change. Trough the association, women reaffirm themselves and their role in the society, conquering their share of the pie in a normally men dominated environment.